Genera of Belytinae (Hymenoptera: Diapriidae) recorded in the Atlantic Dense Ombrophilous Forest from Paraíba to Santa Catarina, Brazil - Quadros, Alex Leite; Brandão, Carlos Roberto F. (Papéis Avulsos de Zoologia, 2017)
The parasitoid wasps Belytinae (Hymenoptera: Diaprioidea: Diapriidae) recorded thus far in the Atlantic Dense Ombrophilous Forest are reviewed at the supra specific level. The knowledge about the diversity of Belytinae in the Atlantic Forest is relatively poor, although these parasitoids may play a key role in the natural regulation of populations of the Mycetophilidae and Sciaridae (Diptera). The material used in this study comes mostly from standardized collections in 18 regularly spaced sites, from Paraíba to Santa Catarina Brazilian states, between 2000 and 2002, by the project “Richness and diversity of Hymenoptera and Isoptera along a latitudinal gradient in the Atlantic Forest – the eastern Brazilian rain forest” (Biota/SP – FAPESP). At each location ten Malaise traps and a hundred Moericke traps were installed, both along two parallel transects spaced 100 m from each other. Further, a similar effort for the sweeping of vegetation was applied at each locality, being each sweeping sample the result of 5 minutes of sweeping. Traps, and sweeping of vegetation in the summed localities yielded a total of 1,241 Belytinae specimens, of which we recognize 115 morphospecies in eight genera (Aclista, Belyta, Cinetus, Odontopsilus, Scorpioteleia, Lyteba, Tropidopsilus and Camptopsilus). A further belytine genus (Miota), recorded in similar environment, was found at the collection of the Federal University of Espírito Santo and added to the list, totalling nine here keyed genera; for each genus we include a diagnosis, comments and a discussion on its records, distribution and biology; we also provide twenty-two plates with 102 figures (93 photographs and 9 maps).